PENERAPAN E-MARKETING DALAM PENINGKATAN KUNJUNGAN DAN LOYALITAS WISATAWAN DI KAWASAN TULAMBEN - Suardana, I.W.; Ariani, N.M.; Dewi, N.G.A.S.; Darsana, I.W. (Buletin Udayana Mengabdi, 2018)
The role of e-marketing in the tourism industry is enabling the distribution channel with the participation of online activities of small and medium enterprises in the tourism industry reached 96.5%. One medium that can be developed as a media campaign is a social media such as, blooging, twitter, facebook, instragram, flicksd, etc. This media are secondary media beside the website or portal of the industry made specifically for the promotion of tourism. The purpose of this community services is to provide training and knowledge of e-marketing to be done in increasing tourist visits to Tulamben. The method used is practice in the field so that the 30 participants can see and understand, and applied the knowledge provided. Social media has three power that social media is not commercial, social media can do the best for public relations and a strong brand has its advantages and strengthen new customers. It is found out from of the service that social media have provided strong recommendations on the new travelers, the purchase decision to come soon, and maintain the loyalty of tourists who revisited the area. Control of the content to build intention to visit and curiosity, becomes very important. Therefore, information and pictures are highly needed to build a good image of tourism in Tulamben.